Asian irrigation, African rain: Remote impacts of irrigation. Issue 8 (20th April 2016) - de Vrese, Philipp; Hagemann, Stefan; Claussen, Martin
Abstract: Irrigation is not only vital for global food security but also constitutes an anthropogenic land use change, known to have strong effects on local hydrological and energy cycles. Using the Max Planck Institute for Meteorology's Earth System Model, we show that related impacts are not confined regionally but that possibly as much as 40% of the present‐day precipitation in some of the arid regions in Eastern Africa are related to irrigation‐based agriculture in Asia. Irrigation in South Asia also substantially influences the climate throughout Southeast Asia and China via the advection of water vapor and by altering the Asian monsoon. The simulated impact of irrigation on remote regions is sensitive to the magnitude of the irrigation‐induced moisture flux. Therefore, it is likely that a future extension or decline of irrigated areas due to increasing food demand or declining fresh water resources will also affect precipitation and temperatures in remote regions. Key Points: Impact of irrigation extents over several thousand kilometers Two responsible mechanisms are advective water vapor transport and shifts in supraregional patterns Decline/increase in irrigation will likely result in reduction/increase in precipitation in remote regions